Antinociceptive and anti-inflammatory activity of extracts and α-pyrones isolated from Cantinoa stricta - Barbosa, Felipe Lukacievicz; Ehrenfried, Carlos Augusto; Radulski, Débora Rasec; Oliveira, Cristhian Santos; Stefanello, Maria Élida Alves; Zampronio, Aleksander Roberto (Inflammopharmacology, 2024)
This study evaluated the composition and the antinociceptive and anti-inflammatory activity of the crude extracts and two isolated compounds, anamarine (ANA) and 10- epi -olguine (eOL), obtained from the leaves of Cantinoa stricta (Lamiaceae). Crude ethanolic extract (EEt) and dichloromethane extract (DCM), selected based on NMR data, were submitted to pharmacological tests in male Swiss mice. The oral administration of EEt and DCM significantly reduced the second phase of formalin-induced nociception (60%), lipopolysaccharide (LPS)-induced mechanical hyperalgesia (90%), and carrageenan (Cg)-induced edema (25%). ANA and eOL, the major compounds in EEt and DCM extracts, administered orally or locally (in the paw), also reduced the LPS-induced mechanical hyperalgesia (Oral ID 50 1.9 and 3.9 mg/kg; Local ID 50 93.4 and 677.3 ng, respectively) without changing the thermal acute nociception or the motor performance of the animals. Local administration of ANA and eOL also reduced Cg-induced edema (40 and 23%, respectively). These isolated compounds did not change the mechanical hyperalgesia induced by tumor necrosis factor-α, interleukin-1β, prostaglandin E2, dibutyryl cyclic AMP, or forskolin but reversed the hyperalgesia induced by dopamine, epinephrine, and phorbol 12-myristate 13-acetate. The hyperalgesia induced by epinephrine was reversed in male but not in female mice, in which this response is not dependent on protein kinase C (PKC). These results suggest that C. stricta extracts possess antinociceptive and anti-inflammatory activity which is related to the presence of ANA and eOL. Differently from the known analgesics, these substances seem to exert their action mainly interfering with the sympathetic component of pain, possibly with PKC.